A concepção de amor como arte e a sua relação com a fé = The conception of love as art and its relationship to faith : contributions of Erich Fromm’s thought: contribuições do pensamento de Erich Fromm - Formiga, Denis Cotta (Plura, revista de estudos de religião, 2020)
This article aims to approach Erich Fromm's conception of love in its relation to faith. For Fromm, love should be seen as an internal activity of the subject, based on the idea of loving the other primordially. The act of loving, according to the author in focus, should be considered a productive activity, which is based on an improvement of the psychic and emotional potentialities of the subject. Moreover, according to Fromm, in order to truly love, faith is needed, which is conceived as a trait of character and thus liable to development. In this sense, the German psychoanalyst reiterates that the act of loving must be understood as an art, which is based on a process of continuous improvement. Regarding the methodology, this study intends to undertake an analytical reading of the works The Art of love, Man for himself and The revolution of hope, all authored by Erich Fromm, besides using the works of commentators of humanistic psychoanalyst. As main objective, this article intends to elucidate the contributions of Frommian’s thought to the relationship between faith and the act of loving. We intend to show that, according to Fromm, for the mastery of the art of loving, it is necessary that the subject improves his character in favor of a productive orientation, that is, the individual must break with narcissism through rational faith, develop the humility to recognize your own limitations and potentialities, and use reason as an instrument that allows you to see the person loved as she or he really is, and not how I wish the person were.